Hubungan Kausalitas Antara Sektor Keuangan Dan Sektor Riil di Indonesia - Fransisca Bernadetta Gunawan (Universitas Kristen Maranatha, 2019)
Economic activities in the real sector is very important, because it has a strong connection with consumption, jobs, and income. The financial sector has the important task to be an intermediary to facilitate the real sector for obtaining funds. The purpose of this study is to see the causal relationship of the financial sector with the real sector of Indonesia from 1986-2015. By using the VAR (Vector Auto Regression) method, the results show that unemployment and banking sector, unemployment and capital market as well as GDP and banking sector have bi-directional causality pattern, whereas capital market and GDP in Indonesia has a one-way causality pattern. Keywords: Financial Sector, Real Sector, VAR